PERFORMANCE EVALUATION OF BRIQUETTES DEVELOPED FROM AGRO-WASTES USING FULL FACTORIAL DESIGN - Istifanus, A.B.; Abutu, J.; Kire, C.E. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study was conducted using palm kernel shells and cassava starch as filler and binder material respectively for the production of carbonized and uncarbonized agro-based briquettes, with the aim of investigating the effects of varying compositions of constituents on the performance of briquettes using constant process parameters of moulding pressure (10MPa). The treatments consisted of moulding temperature (120oC), curing time (5 mins) and heat treatment time (1hr), these were laid out in a 2-level full factorial design (L422). The results of the experiment revealed that, change in percentage composition of the developed briquettes affects the performance of the briquettes. However, lower values of hardness were recorded for carbonized based briquettes compared to uncarbonized based briquettes which may be attributed to the higher dendrite size and formation of coarse grains structure in the composite. Also, the use of carbonized or uncarbonized palm kernel shell as filler materials produced an optimal ash, moisture and volatile content which composed of 220g fillers (carbonized or uncarbonized) and 100g binder (cassava starch) representing 63% and 29% of the entire composition respectively. The study further revealed that, fixed carbon of briquettes can be achieved with fillers (200g) and cassava starch (150g) representing 57% and 43% of the entire composition respectively. Based on the results obtained, it can be concluded that the uncarbonized palm kernel shell-based briquettes performed better and possess good hardness compared to the carbonized based briquettes. However, in the future, the two filler materials (carbonized and uncarbonized palm kernel shells) should be set as experimental factor along with cassava starch so as to statistically evaluate combined significance in performance of the briquettes.